2010
DOI: 10.1186/1550-2783-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the efficacy of acute L-alanyl-L-glutamine ingestion during hydration stress in endurance exercise

Abstract: BackgroundThe effect of acute L-alanyl-L-glutamine (AG; Sustamine™) ingestion on performance changes and markers of fluid regulation, immune, inflammatory, oxidative stress, and recovery was examined in response to exhaustive endurance exercise, during and in the absence of dehydration.MethodsTen physically active males (20.8 ± 0.6 y; 176.8 ± 7.2 cm; 77.4 ± 10.5 kg; 12.3 ± 4.6% body fat) volunteered to participate in this study. During the first visit (T1) subjects reported to the laboratory in a euhydrated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 57 publications
5
32
0
2
Order By: Relevance
“…Participants were also required to cycle to exhaustion at 75% of VO 2max . The investigators reported significantly greater times to exhaustion in participants who were provided the dipeptide compared to a no-fluid trial [16]. Time to exhaustion was not significantly different between the no-fluid trial and water-only trial.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Participants were also required to cycle to exhaustion at 75% of VO 2max . The investigators reported significantly greater times to exhaustion in participants who were provided the dipeptide compared to a no-fluid trial [16]. Time to exhaustion was not significantly different between the no-fluid trial and water-only trial.…”
Section: Introductionmentioning
confidence: 93%
“…Glutamine is a nonessential amino acid and is involved in many physiologic functions, including cellular proliferation, acid-base balance, transport of ammonia between tissues, and antioxidant synthesis [15]. It has been used in both medical and athletic settings to try to enhance fluid absorption [16][17][18][19]. During prolonged starvation, sepsis, and long-duration physical activity, glutamine concentrations may become deficient [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is glutamine in many physiologic functions including cellular proliferation, acid-base balance, transport of ammonia between tissues, and antioxidant synthesis [1][2][3]. Glutamine supplementation stimulates an increase in protein synthesis in the muscle, improves glycogen re-synthesis and can lead to an improvement in performance [4,5]. Glutamine has been shown to increase fluid and electrolyte absorption in both animal and human models [6].…”
mentioning
confidence: 99%
“…Glutamine has been shown to increase fluid and electrolyte absorption in both animal and human models [6]. Recently, consumption of an alanine-glutamine dipeptide was reported to enhance fluid uptake and reduce the magnitude of performance decrement during exercise to exhaustion under hypohydrated conditions [5]. Furthermore, the alanine-glutamine dipeptide was shown to be significantly more effective than water alone.…”
mentioning
confidence: 99%